Gobio baliki, a new gudgeon from Turkey (Teleostei: Cyprinidae) - Turan, Davut; Kaya, Cüneyt; Bayçelebi̇ Esra; Aksu İsmai̇l; Bektaş, Yusuf (Zootaxa, 2017)
Gobio baliki, new species, is described from the stream Büyük Melen in the northwestern Anatolian Black Sea basin. The new species is distinguished from other gudgeons in Anatolia by the breast being completely covered by scales, scales extending slightly behind the isthmus; 5–6 scales between the posterior extremity of the pelvic-fin base and the anus; the distance between the anus and the anal-fin origin 7–10% SL; the postorbital distance equal to or greater than the snout length; the depth of the anal-fin approximately equal to the length of the pelvic-fin; 8–9 midlateral black blotches, usually separated from each-other